Penerapan Model Pembelajaran Inkuiri untuk Membentuk Habits of Mind Siswa - Masiah, Masiah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This study aims to improve students' habits of mind through the implementation of inquiry learning models. This research is classroom action research (CAR) which consists of stages: (1) action planning, (2) implementation of actions, (3) observation and interpretation, (4) analysis and reflection. The subjects of this study were 30 people. Data collection techniques are carried out by observation, questionnaire, and test. Based on the results of the study, the n-gain of students' habits of mind is 0.62 (medium category), this is captured through questionnaire data given at the beginning and at the end of the learning so that they can know the initial conditions before and after the application of inquiry learning. The results of the student questionnaire in Cycle I were 40%, Cycle II 47% and Cycle III as many as 57% of students who had habits of mind in a good category. Student's N-gain test is 0.73 with a high category and student completeness reaches 83%. Based on the results of the study it can be concluded that the application of inquiry learning models can improve students' habits of mind.